Respuesta :

Answer:

(x - 2)(5x + 3) = 0

Step-by-step explanation:

5x² - 7x - 6 = 0

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 5 × - 6 = - 30 and sum = - 7

The factors are - 10 and + 3

Use these factors to split the x- term

5x² - 10x + 3x - 6 = 0 ( factor the first/second and third/fourth terms )

5x(x - 2) + 3(x - 2) = 0 ← factor out (x - 2) from each term

(x - 2)(5x - 3) = 0 ← in factored form

ACCESS MORE